Immune thrombocytopenia associated with tuberculosis – A case report. (2021) - Khan, Adeel Ahmad; Shahzad, Aamir; Javid, Haleema; Fatima, Tehreem; Yousaf, Zohaib
Abstract: Tuberculosis can involve the hematological system and cause anemia, leucopenia, leukocytosis, thrombocytopenia, and thrombocytosis. Immune thrombocytopenia related to tuberculosis is rare. We present a case of a 54 years old male patient who was evaluated for isolated asymptomatic thrombocytopenia discovered on routine laboratory investigations. Work up was positive for disseminated tuberculosis. The patient responded to a tapering dose of steroids and anti-tuberculous medications with significant and persistent platelet count improvement.